1990
DOI: 10.2135/cropsci1990.0011183x003000010009x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Among Pearl Millet Landraces Collected in Central Burkina Faso

Abstract: Evaluation of genetic diversity within germplasm collections is important to plant breeders who desire sources of genes for particular traits. The S1 bulks of 103 landraces of pearl millet [Pennisetum glaucum (L) R. Br.] collected in central Burkina Faso, West Africa were evaluated for morphologic characteristics in an attempt to differentiate among the landraces. Seed shape, seed color, and 100 seed weight were evaluated. Maturity and height of field‐grown plants were assessed in 1987 and 1988, and panicle le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The maximum number of accessions (82) were included in cluster I, whereas clusters III -VII and IX -XII contained only one accession each, which would indicate extreme phenotypic performance in a positive or negative direction for one, or the other character. Cluster I included accessions from all sources, indicating that there was no association between pattern of clusters and geographical distribution of accessions, and this agrees with earlier findings of Thete et al (1986), Joshi et al (1988) and Wilson et al (1990). Considering the intra and inter-cluster distances (Table 03) the maximum inter-cluster distance was recorded between cluster XI and XII.…”
Section: Resultssupporting
confidence: 90%
“…The maximum number of accessions (82) were included in cluster I, whereas clusters III -VII and IX -XII contained only one accession each, which would indicate extreme phenotypic performance in a positive or negative direction for one, or the other character. Cluster I included accessions from all sources, indicating that there was no association between pattern of clusters and geographical distribution of accessions, and this agrees with earlier findings of Thete et al (1986), Joshi et al (1988) and Wilson et al (1990). Considering the intra and inter-cluster distances (Table 03) the maximum inter-cluster distance was recorded between cluster XI and XII.…”
Section: Resultssupporting
confidence: 90%
“…[15] identified based on isozyme markers two distinct sub-groups in pearl millet inbreds from West Africa, whereas [19] reported three sub-groups for pearl millet landraces from Niger. In contrast, [1] identified based on phenotypic data of morphological and disease resistance traits ten clusters of pearl millet landraces from Burkina Faso. These differences in the number of sub-groups compared to our study, are most likely due to the fact that earlier studies examined a lower number of accessions than we did.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, it has been shown that in other parts of the world farmers also use a wide range of rice varieties (Richards 1986;Lambert 1985;Dennis 1988). In the case of pearl millet, farmers in Nigeria and Burkina Faso use a wider range of millet varieties compared to The Gambia (Busso et al 2000;Wilson et al 1990). This difference in variety use between rice and millet can be explained by the breeding systems of the two crops, rice being a self-pollinator and millet a cross-pollinator, and by the greater complexity of ecological conditions for rice compared to those for millet.…”
Section: Homonyms and Synonymsmentioning
confidence: 99%